Prevalence and risk factors predisposing low bone mineral density in patients with thalassemia - Ananvutisombat, Natnicha; Tantiworawit, Adisak; Punnachet, Teerachat; Hantrakun, Nonthakorn; Piriyakhuntorn, Pokpong; Rattanathammethee, Thanawat; Hantrakool, Sasinee; Chai-Adisaksopha, Chatree; Rattarittamrong, Ekarat; Norasetthada, Lalita; Fanhchaksai, Kanda; Charoenkwan, Pimlak (Frontiers in Endocrinology, 2024)
Background A common complication of thalassemia is secondary osteoporosis. This study aimed to assess the prevalence and factors associated with low BMD in thalassemic patients. Method This is a cross-sectional study. Eligible patients were males aged within 18–49 years or premenopausal women diagnosed with thalassemia in Chiang Mai University Hospital between July 2021 and July 2022. The diagnosis of low BMD by dual-energy x-ray absorptiometry (DXA) was defined as a Z-score of -2.0 SD or lower in either the lumbar spine or femoral neck. Clinical factors associated with low BMD were analyzed using a logistic regression model. Results Prevalence of low BMD was 62.4% from 210 patients with a mean age of 29.7 ± 7.6 years. The predominant clinical characteristics of low BMD thalassemia patients were being female, transfusion-dependent (TDT) and a history of splenectomy. From multivariable analysis, the independent variables associated with low BMD were transfusion dependency (odds ratio, OR 2.36; 95%CI 1.28 to 4.38; p=0.006) and body mass index (BMI) (OR 0.71; 95%CI 0.61 to 0.82; p<0.001). Among patients with low BMD, we observed a correlation between a Z-score with low IGF-1 levels (β=-0.42; 95% CI -0.83 to -0.01; p=0.040), serum phosphate levels (β=0.40; 95% CI 0.07 to 0.73; p=0.016) and hypogonadism (β=-0.48, 95% CI -0.91 to -0.04, p=0.031). Conclusion This study found a prevalence of low BMD in 62.4% of subjects. Factors associated with low BMD were TDT and BMI. Within the low BMD subgroup, hypogonadism, serum phosphate and low serum IGF-1 levels were associated with a lower Z-score.